Fulfillment of Workers' Rights to Rest and Leave in Employment Relations According to Labor Law - Maria MT Manurung; Diah Syafitri Siregar (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
Problems in employment relations are often characterized by the failure to fulfill workers' rights to rest and leave, even though these rights play a crucial role in maintaining worker health and maintaining company productivity. This situation indicates a gap between normative regulations and actual employment practices. This study aims to examine employers' obligations to fulfill workers' rights to rest and leave under Indonesian labor law, and to examine the forms of legal protection available to workers in the event of violations of these rights. The research method used is normative juridical research with a statutory approach and a literature review of relevant laws and regulations. The results indicate that the right to rest and leave is a normative worker right that employers must fulfill, as stipulated in Law Number 13 of 2003 and Government Regulation Number 35 of 2021. Violations of these provisions can result in administrative and criminal sanctions for employers. Legal protection for workers is provided through labor supervision and industrial relations dispute resolution mechanisms. This study confirms that effective supervision and clear regulations in company regulations are necessary to ensure the fulfillment of workers' rights to rest and leave.